Heterostructures with Built‐in Electric Fields for Long‐lasting Chemodynamic Therapy. Issue 15 (2nd March 2023) - Zhang, Huilin; Chen, Yang; Hua, Wei; Gu, Wenjun; Zhuang, Hongjun; Li, Huiyan; Jiang, Xingwu; Mao, Ying; Liu, Yanyan; Jin, Dayong; Bu, Wenbo
Abstract: Sustained signal activation by hydroxyl radicals (⋅OH) has great significance, especially for tumor treatment, but remains challenging. Here, a built‐in electric field (BIEF)‐driven strategy was proposed for sustainable generation of ⋅OH, thereby achieving long‐lasting chemodynamic therapy (LCDT). As a proof of concept, a novel Janus‐like Fe@Fe3 O4 −Cu2 O heterogeneous catalyst was designed and synthesized, in which the BIEF induced the transfer of electrons in the Fe core to the surface, reducing ≡Cu 2+ to ≡Cu +, thus achieving continuous Fenton‐like reactions and ⋅OH release for over 18 h, which is approximately 12 times longer than that of Fe3 O4 −Cu2 O and 72 times longer than that of Cu2 O nanoparticles. In vitro and in vivo antitumor results indicated that sustained ⋅OH levels led to persistent extracellular regulated protein kinases (ERK) signal activation and irreparable oxidative damage to tumor cells, which promoted irreversible tumor apoptosis. Importantly, this strategy provides ideas for developing long‐acting nanoplatforms for various applications. Abstract : A long‐lasting chemodynamic therapy strategy for achieving sustained efficient tumor treatment was developed by synthesizing Janus‐like Fe@Fe3 O4 −Cu2 O heterostructures with built‐in electric fields (BIEFs). Driven by the BIEFs, electrons in the Fe 0 core were continuously transferred to the surface to reduce ≡Cu 2+ to ≡Cu +, thus ensuring a sustained Fenton‐like reaction and ⋅OH production and forcing tumor cells to undergo apoptosis through ERK signal activation.